Influencia de los programas televisivos en el comportamiento escolar de los estudiantes de séptimo año de educación básica de la “Escuela 5 de Junio” de la Parroquia Isla de Bejucal del cantón Baba, Provincia de Los Ríos - Soto Preciado, Yarima María (2019)
This research work refers to television programs from the educational approach allow the student to establish emotions; However, when they achieve them, they have another point of view in which they harm the values. The approach of the case study used was quantitative and qualitative, with a transversal descriptive plan, although there is no definitive answer, the evidence shows that television has significant effects on aggressive behavior, but doubts remain about the conditions under which these occur. Effects. As a global social phenomenon, the relationship between television media and audience behavior transcends the analysis and intervention of individual behavior, so it is necessary to use a more integrative and interdisciplinary framework to explain and predict the effects. The techniques and instruments used were: a survey of the perception of teachers, parents and an interview with children about the influence of television programs on aggressive behavior that allowed to know the problems that occur in said school. The relationship on the addiction of violent television programs and the behavior of children and adolescents has been a topic of interest for the different studies involved in the analysis and intervention on collective social behavior. In this way, this research verifies the evidence that supports the hypothesis of the adverse effects of television, which shows a framework with affability to understand the effect of television programs from a cultural, educational point of view and explains the effects that entail to the analysis of television programs